Sustainability Reporting : Analisis Kinerja Keuangan dan Nilai Perusahaan - Anna, Yane Devi; Dwi R.T, Dita Rari (Jurnal ASET (Akuntansi Riset), 2019)
Abstract. As more companies in Indonesia publish sustainability reports, the trend of research on the relationship between sustainability reports and financial performance has begun to be carried out. However, most of the research that has been done shows results that have not been consistent. The purpose of this study was to examine the effect of sustainability report which was described as economic performance disclosure, environmental performance disclosure, and social performance disclosure on corporate financial performance and its implications for company value. The study was conducted on winner companies based on NCSR categories and also listed as issuers on the Indonesia Stock Exchange (IDX) during 2015-2017. Research analysis using Partial Least Square (PLS). The results of the study show that Sustainability reporting has an effect on the profitability of disclosures related to aspects of economic performance and environmental performance, while aspects of social performance have no effect on profitability. Sustainability reporting based on aspects of economic, environmental and social performance has an effect on company value. Financial performance cannot mediate the effect of sustainability reporting based on aspects of economic performance, social performance and environmental performance on firm value.Keywords. sustainibility reporting; financial performance; firm valueAbstrak. Seiring dengan semakin banyaknya perusahaan di Indonesia yang mempublikasikan sustainability report, maka tren penelitian tentang hubungan antara sustainability report dan kinerja keuangan mulai banyak dilakukan. Namun demikian, sebagian besar penelitian yang telah dilakukan menunjukkan hasil yang belum konsisten. Tujuan dari penelitian ini adalah untuk menguji pengaruh sustainability report yang dijabarkan menjadi economic performance disclosure, environmental performance disclosure, dan social performance disclosure terhadap kinerja keuangan perusahaan serta implikasinya terhadap nilai perusahaan yang dilakukan Penelitian dilakukan terhadap perusahaan winner berdasarkan kategori dari NCSR dan tercatat pula sebagai emiten pada Bursa Efek Indonesia (BEI) selama 2015 -2017. Analisis penelitian menggunakan Partial Least Square (PLS). Hasil penelitian menunjukan bahwa Sustainability reporting yang berpengaruh terhadap profitabilitas pengungkapan yang berkaitan dengan aspek kinerja ekonomi dan kinerja lingkungan, sedangkan aspek kinerja sosial tidak berpengaruh terhadap profitabilitas. Sustainability reporting berdasarkan aspek kinerja ekonomi, lingkungan dan sosial berpengaruh terhadap nilai perusahaan. Kinerja keuangan tidak dapat memediasi pengaruh sustainability reporting berdasarkan aspek kinerja ekonomi, kinerja sosial dan kinerja lingkungan terhadap nilai perusahaan.Kata Kunci.Â sustainibility reporting; kinerja keuangan; nilai perusahaan